Efektivitas Bahan Ajar E-Modul Berbasis IT dengan Model Problem Based Learning (PBL) pada Mata Pelajaran Kearsipan dalam Meningkatkan Hasil Belajar Peserta Didik di SMK Sunan Giri Menganti - Risky Octa Vianis; Waspodo Tjipto Subroto; Susanti Susanti (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
This study has the aim of testing the effectiveness of IT-based e-modules with Problem Based Learning (PBL) models in archiving subjects in order to improve student learning outcomes in class X OTKP SMK Sunan Giri Menganti. The approach used in this study is quantitative with experimental types of pretest-posttest control group. The research subjects include the experimental group namely X OTKP 1 and the control group namely X OTKP 2, totaling 20 students in each group. The data analysis technique used in this study is the N-Gain test to measure the effectiveness of learning outcomes. The results of this study are the average value of the experimental group, which is 0.84 or 84.12%, this shows that the value of the experimental group belongs to the high category and is effectively interpreted. While the average value of the control group is 0.41 or 40.70% is included in the medium category and is less effective. So learning to use IT-based e-modules with PBL models is more effective than conventional learning or lecture methods using Google Meet, Zoom, or WhatsApp.